Severe Acute Fatty Liver of Pregnancy (AFLP) Associated with Unknown Factor VII Deficiency - Bonino, Luca; Vasario, Elena; Ballario, Paola; Rapezzi, Andrea; Clignon, Valentino; Uccella, Stefano; Puppo, Andrea (Archives of Clinical and Medical Case Reports, 2022)
We present a case of acute fatty liver of pregnancy (AFLP) associated with unknown factor VII deficiency. The final diagnosis for our patient, a 28 year old female, G2P1, has been a challenge and required multiple treatments included a postpartum emergent laparotomy with haemostatic hysterectomy. Multidisciplinary approach with other specialists was crucial for the outcome of this patient who required a massive amount of resources both diagnostically and therapeutically